Vibrational spectra of Zn(II) complexes of the amino acids with hydrophobic residues - Wagner, Claudia Cecilia (2009)
The infrared and Raman spectra of the bis-chelated Zn(II) complexes of the amino acids glycine, alanine, valine, leucine, isoleucine and phenylalanine were recorded and analyzed in relation to its structural peculiarities. Some comparisons between the recorded spectra are also presented and the characteristics of the carboxylate motions as well as those of the metal-to-ligand vibrations are discussed in detail.